Investigating proactive balance control in individuals with incomplete spinal cord injury while walking on a known slippery surface. (1st April 2021) - Bone, Mackenzie D.; Arora, Tarun; Musselman, Kristin E.; Lanovaz, Joel L.; Linassi, Gary A.; Oates, Alison R.
Highlights: The iSCI group walked slower with shorter, flatter steps in all conditions. Both groups (AB and iSCI) employ proactive balance strategies in a similar manner. Both groups made proactive adaptations after just one slip experience. The proactive adaptations were maintained throughout all expected slip trials. The proactive adaptations were effective at reducing slip severity. Abstract: Background: Up to 83 % of individuals with incomplete spinal cord injury (iSCI) experience ≥ 1 fall/year. Individuals with iSCI employ more cautious walking strategies than able-bodied (AB) individuals during normal walking. Whether individuals with iSCI can use proactive balance strategies to adapt to expected slip perturbations/reduce slip severity while walking has not been previously assessed. Methods: 19 individuals with iSCI (AIS D; 14 males; 61 ± 18 years) and 17 AB individuals (13 males; 61 ± 18 years) completed 3 walking conditions: normal walking trials, an unexpected slip trial, and expected slip trials. Steel rollers induced a slip in the antero-posterior (AP) direction. Outcome variables included step length, center of mass velocity, foot-floor angle, AP margin of stability, and maximum post-slip velocity (PSV). Results: The iSCI group used a greater magnitude of cautious strategies (i.e. walking slower with shorter, flatter steps) than AB individuals in all conditions. However, the lack of significant interaction effects indicate that the proactive adaptations compared to normal walking (i.e. walking slower with shorter, flatter steps, and a more anterior xCOM-position) were similar between the two groups (AB & iSCI). Both groups showed a similar rate of adaptation (after just 1 slip) and these feedforward changes were maintained throughout the remaining slip trials which was effective at reducing maximum PSV. Conclusions: Individuals with iSCI use proactive balance strategies to adapt to a known slippery surface in a similar manner to AB individuals both in terms of the proportion and timing of adaptation.